Fungal endophyte Cryptomycina pteridis (Rebent.) Syd. on the native fern Pteridium aquilinum (L.) Kuhn in Poland - Zenkteler, Elżbieta; Celka, Zbigniew; Szkudlarz, Piotr; Grzegorzek, Piotr (Biodiversity: Research and Conservation, 2023)
Cryptomycina pteridis (Ascomycota, class Sordariomycetes) is a highly host-specific fungus, infecting only a native, fern Pteridium aquilinum. This endophyte is usually overlooked, although it is easy to recognise due to its characteristic symptoms on bracken fern fronds, especially advanced narrowing and shrivelling of pinnae and pinnules. Infested plants have pinnae and pinnules curling upwards, and dark stromata along the veins on the undersides of pinnules. The fungus is an obligate systemic endophyte, which disturbs fern growth. The paper presents some old and new records of C. pteridis in Poland.